ISLAMISM AND CONTEMPORARY INDONESIAN ISLAMIC POLITICS - Zuly Qodir; Jubba, Hasse; Mega Hidayati (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2022)
After the 2019 election, Indonesia is facing changes in political and religious life. In political life, the use of ethnic identity appears as a voter. Meanwhile, in terms of religion, the forces of Islamic conservatism and populism have emerged that have disrupted electoral democracy. The issue of identity politics, Islamic conservatism and populism will continue to grow if the moderate Islamic forces of Muhammadiyah and NU do not appear in political and religious life. The hope of a civilized and non-discriminatory democratic life in the strength of moderate Islam. If the power of moderate Islam is weak, then the power of Islamic conservatism with the power of identity politics and Islamic populism will become a real form of challenge to Indonesian democracy. This article aims to explain the three main challenges of Indonesian democracy after the 2019 Presidential Election, namely the rise of Identity politics; the rise of political Islamism which is compounded in Indonesian political practices. How both of them come into contact with political practices in Indonesia, so that it has an impact on Islamic politics today. ملخص توجه الإندونيسيا تفرق الحياة السياسية و الدينية بعد الانتخاب العامي سنة ٢٠١٩ حيث ظهرت هوية العرقية في الحياة السياسية كعاملة منجمة الصوت، بينما في الحياة الدينية ظهرت قوة المحافظة و الشعوبية الإسلامية تتدخل في الديمقراطية الانتخابية. صارت سياسات الهوية و المحافظة والشعوبية الإسلامية دائما تتطور إذا كانت قوة الوسطية الإسلامية المحمدية و نهضة العلماء غير مرئية أمام الحياة السياسية والدينية. كان الأمل بالحياة الديمقراطية حضارية و غير تمييزة في قوة الإسلام المعتدل. إذا ضعفت قوة الإسلامية الوسطية ستصبح قوة التيار الإسلامي المحافظ بقوة سياسات الهوية والشعبوية الإسلامية شكلاً حقيقيًا من أشكال التحدي للديمقراطية الإندونيسية. هذا المقال سيبين ثلاث التحديات الأولى في الديمقراطية الإندونيسية بعد الانتخاب العامي لرئيس الجمهور سنة ٢٠١٩ وهو ايقاظ سياسات الهوية و الإسلام السياسي الذي يتحد في ممارسة السياسة الإندونيسية و كيف يتعامل كلاهما في السياسة الإندونيسية بحيث يكون لها تأثير في السياسة الإسلامية اليوم.